Reintepretasi terhadap Ayat-Ayat Khamr dalam Al-Qur’an: Analisis Intertekstual Julia Kristeva - Yulianda, Reno (Contemporary Quran, 2022)
It is known that the problem of alcoholic beverages has been prevalent in the past and is still prevalent today. This action leads to many bad things that can damage yourself and cause others. This article seeks to give new thoughts on real or existing problems in the Qur'an. Efforts to explore or analyze the text of the Qur'an, especially discussing alcohol, can be reviewed from a literary (language) perspective, also known as semiotics. This research wants to see how the role of Julia Kristeva's semiotics with its intertextuality approach theory to reveal and trace from one text to another related to the discussion being studied. So it takes a type of qualitative research that is literature in which the collection of data is taken from books, scientific works, especially those related to liquor. The purpose of applying Julia Kristeva's intertextuality theory is to analyze the data that has been collected in order to reveal the transformations, modifications and parallels that occur from all texts. The results obtained from Julia Kristeva's intertextuality theory regarding liquor. There are transformations, modifications and parallels that occur in the three verses about liquor, namely QS. Al-Baqarah (2): 219, QS. An-Nisa' (4): 43 and QS. Al-Ma'idah (5): 90-91. The first verse warns that intoxicants contain many evils and harms. The second verse explains that it is not recommended to pray while drunk. It is known that the habits of the Arab community at that time could not be separated from liquor, even when they wanted to pray. This is the transformation and modification that occurs in the first verse to the second verse. The parallel is known in the previous two verses and this third verse both discuss liquor, but in this verse there is a meaning of confirmation of the prohibition of liquor.